2023
DOI: 10.17507/tpls.1312.29
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of Gaza War (2021) in the Official Remarks of Hamas and Israel: A Critical Discourse Study

Hamza K. Alnwihe,
Linda S. Al-Abbas

Abstract: This study investigated the representation of Gaza War (2021) in the official remarks of Hamas and Israel. All remarks released over the 11-day war were collected and analysed according to Van Dijk's (2006) ideological square to explore the discursive strategies that each party utilized and uncover the possible hidden ideologies. Two main strategies were employed in the speeches, namely, emphasizing our good things and emphasizing their bad things. The collected examples generated different themes including pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results of his research showed that there were two media that published news about student bullying at UIN Jambi which portrayed women positively, namely, Kompas.com and Republika.co.id while Detik.com portrayed women negatively. Second, research conducted by Alnwihe & Al-Abbas (2023) with the title "The Representation of Gaza War (2021) in the Official Remarks of Hamas and Israel: A Critical Discourse Study". The results of the research show that each party tends to present themselves positively and the other party negatively.…”
Section: Introductionmentioning
confidence: 99%
“…The results of his research showed that there were two media that published news about student bullying at UIN Jambi which portrayed women positively, namely, Kompas.com and Republika.co.id while Detik.com portrayed women negatively. Second, research conducted by Alnwihe & Al-Abbas (2023) with the title "The Representation of Gaza War (2021) in the Official Remarks of Hamas and Israel: A Critical Discourse Study". The results of the research show that each party tends to present themselves positively and the other party negatively.…”
Section: Introductionmentioning
confidence: 99%